The use of large loop excision of the transformation zone (LLETZ) in an outpatient setting - Powell, B (Australian & New Zealand journal of obstetrics & gynaecology, 1996)
An audit of the results of 129 patients treated in the first 12 months of operation of an outpatient large loop excision of the transformation zone (LLETZ) clinic was performed. It confirmed the efficacy of the procedure in treatment of cervical intraepithelial neoplasia (CIN) with a cure rate of 93.8%. Major deficiencies identified were the lack of compliance with recommended follow-up, a major discrepancy between predicted diagnosis on colposcopically directed punch biopsy and LLETZ specimen histology, and a large proportion of LLETZ specimens which had negative histology and may be regarded as overtreatment. Suggested strategies to address these include observation of low-grade lesions and treatment with LLETZ at the first clinic appointment.